2020
DOI: 10.1111/hsc.12924
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering strengths within community dwelling older adults: What does it mean for health care practice?

Abstract: The aim of this paper is to present the psychological strengths we identified from interviews with community dwelling older adults. Data for this paper is drawn from participants in a community dwelling older adult study. The latter involved qualitative in‐depth interviews with the participants exploring their well‐being. All participants were community dwelling and living in a region in the North Island of New Zealand. Interviews took place between March 2017 to September 2017. Thirty‐seven older adults betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Modesty means an unwillingness to praise oneself and show off one’s qualities or achievements. 2 36 In all of our interviews, when we first mentioned expressing personal strengths, the participants often avoided talking and reflected that humility is a common occurrence. The participants were reluctant to talk about their own achievements and character strengths.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Modesty means an unwillingness to praise oneself and show off one’s qualities or achievements. 2 36 In all of our interviews, when we first mentioned expressing personal strengths, the participants often avoided talking and reflected that humility is a common occurrence. The participants were reluctant to talk about their own achievements and character strengths.…”
Section: Resultsmentioning
confidence: 96%
“…Studies of different cultures have revealed character strengths in different populations, including adolescents, 17 college students, 18 adults 6 and the elderly. 2 The classification model has been validated in 75 nations, with each sample including at least 150 respondents; these findings suggest substantial cross-cultural similarity in strengths. 19 Virtues are classes of character strengths that show individual differences but relative cross-cultural stability.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the current longitudinal study CD predicted ISS, supporting the hypothesis that having a disease and/or going through a crises in life positively affects inner strength over time. Of interest may be that Waterworth et al ( 2020 ) found that old people had difficulty identifying and discussing their strengths. The measure of inner strength used in this study is based on how old people describe their perceptions of their own connectedness to others (e.g., if they see themselves as part of a community, and if they can seek support from others when in a difficult situation).…”
Section: Discussionmentioning
confidence: 99%